One-step synthesis of highly porous nitrogen doped carbon from the direct pyrolysis of potassium phthalimide for CO2 adsorption. Issue 39 (July 2020) - Shi, Jinsong; Cui, Hongmin; Xu, Jianguo; Yan, Nanfu; Liu, Yuewei; Zhang, Shaowei
Graphical abstract: Highlights: Nitrogen doped carbon is synthesized from potassium phthalimide in one-step. The specific surface area of the carbon reaches 2053 m 2 /g. The nitrogen content of the carbon is 3.3–9.1 wt%. CO2 uptake at 0.15 bar and the adsorption selectivity show a linear relationship. Abstract: In the current work, we reported the synthesis of nitrogen doped carbons (NDCs) with a very convenient one-step strategy. Highly porous NDCs were successfully prepared from the direct pyrolysis of potassium phthalimide at 600−900 °C. The obtained carbon had a high specific surface area (2053 m 2 /g) and pore volume (1.14 cm 3 /g) after pyrolysis at 900 °C. The nitrogen content of the carbon was 3.3–9.1 wt%, and decreased with the increase of pyrolysis temperature. The combination of high porosity and nitrogen content made the synthesized NDCs attractive CO2 adsorbents. At 25 °C, the carbon exhibited CO2 uptakes of 1.1 mmol/g at 0.15 bar, and 3.4 mmol/g at 1 bar. The experiment results also revealed a linear relationship between the uptake at 0.15 bar and the CO2 /N2 adsorption selectivity. Small micropores and nitrogen containing functionalities had decisive effects on these properties.